Pengaruh Dewan Komisaris Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening - Abdul Kadir Usry; Tutik Arniati; Muslichah (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2022)
This study aims to examine the effect of the board of commissioners (BOC) and capital structure on firm value. This research is a quantitative research, the data is processed using SMART-PLS. The population of this research are banking companies. By using purposive sampling technique, 37 banks were obtained as samples. if the period used is 3 years, the total observation is 111. Research findings indicate that BOC has a positive effect on firm value. Furthermore, the BOC has a negative influence on the capital structure. The next finding is that capital structure has a significant negative effect on firm value. Finally, capital structure mediates the effect of BOC on firm value.